The Association Between Previous TORCH Infections and Pregnancy and Neonatal Outcomes in IVF/ICSI-ET: A Retrospective Cohort Study - Liu, Yifeng; Wu, Yiqing; Wang, Feixia; Wang, Siwen; Zhao, Wei; Chen, Lifen; Tu, Shijiong; Qian, Yuli; Liao, Yun; Huang, Yun; Zhang, Runjv; Xu, Gufeng; et al. (Frontiers in Endocrinology, 2020)
Objective: This study aimed to investigate the associations between previous TORCH infection (Cytomegalovirus, Toxoplasmosis, Herpes Simplex Virus and Rubella) with pregnancy and neonatal outcomes in couples underwent IVF/ICSI-ET. Materials and Methods: A total of 18074 couples underwent fresh IVF/ICSI-ET (In vitro fertilization/Intracytoplasmic sperm injection-Embryo transfer) cycles were included in our analyses. TORCH infection status was determined by serological confirmation of Cytomegalovirus, Toxoplasmosis, Herpes Simplex Virus and Rubella IgG in the absence of IgM antibodies. Clinical pregnancy, ectopic pregnancy, miscarriage, live birth, preterm birth, congenital malformation and perinatal death were evaluated in both infection and none-infection group. Multivariate logistic regression was applied to calculate odds ratio. Results: Previous toxoplasmosis infection is associated with a significantly decreased preterm birth rate (P=0.045, OR=0.755 [95% CI, 0.571-0.997], Adjusted OR=0.749 [95%CI, 0.566-0.991]). No differences in clinical pregnancy, ectopic pregnancy, miscarriage, and perinatal death were observed between the corresponding TORCH infection group (IgM(-) IgG(+)) and the none-infection group (IgM(-) IgG(-)). Conclusions: Previous TORCH infections were not associated with adverse pregnancy and neonatal outcomes in IVF/ICSI-ET overall, and toxoplasmosis infection might be associated with a lower preterm birth rate in patients underwent IVF/ICSI-ET. The necessity of TORCH IgG screening in IVF procedure might need re-evaluation, and further cost-effective analysis might be helpful for the clinical management strategy.